Studying the Features of Legal Consciousness of Criminal Drug Addicts - Kseniya N. Goncharova (Rossijskij psihologičeskij žurnal., 2016)
The article offers the results of the study of legal consciousness of criminal drug addicts. 150 respondents took part in the study. 100 of them (adult male offenders serving sentences in places of confinement) were divided into two groups: drug addicts and non-addicts. 50 adult men with normative behavior (neither criminals nor drug addicts) also took part in the study. The author proceeded from the assumption that criminal drug addicts had some psychological characteristics: a low level of legal consciousness, combined with a high level of risk preparedness, decrease in volitional self-control, which is not conducive to learning and observance of lawfulness. The author used observation, interview, questionnaire, testing; they also reviewed dossiers and medical histories of respondents. There were significant differences between indices in the studied groups. In particular, the level of legal conscience in criminal drug addicts is much lower than in men with normative behavior. Criminal drug addicts are characterized by a high level of risk preparedness, decrease in volitional self-control, lability, anxiety, rigidity of attitudes. The article emphasizes the practical significance of the research results which can be used in the rehabilitation of drug addicts, as well as in preventive measures.